2016
DOI: 10.4012/dmj.2016-039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enamel margin configuration on color change of resin composite restoration

Abstract: This study aimed to investigate the effect of enamel margin configuration on color change of resin composite restoration. Enamel disks of 1.0 mm-thick were sliced from sixty bovine anterior teeth and divided into three groups by margin configuration (non-bevel, 45-degree bevel and 45-degree reverse-bevel). The color measurements (L*C*h* values) at the restored bovine enamel disk with resin composite (Estelite Asteria, Estelite Pro, Kalore, Clearfil Majesty) were performed using a digital camera with CIE XYZ co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 16 publications
0
25
0
1
Order By: Relevance
“…Marginal bevelling is a procedure that can reduce marginal gap formation, improve fracture resistance (Coelho-de- Souza et al, 2008;Soliman et al, 2016), and result in improved esthetics (Aida et al, 2016). Marginal gap formation is the result of a localized failure due to stress concentration or insufficient bond strength (Braga et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Marginal bevelling is a procedure that can reduce marginal gap formation, improve fracture resistance (Coelho-de- Souza et al, 2008;Soliman et al, 2016), and result in improved esthetics (Aida et al, 2016). Marginal gap formation is the result of a localized failure due to stress concentration or insufficient bond strength (Braga et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the enamel margin on colour adjustment has also been investigated [ 39 ]. Three types of enamel margin (non-bevel, 45-degree bevel and 45-degree reverse-bevel) and four composite resin materials (Estelite Asteria A2B, Tokuyama Dental Corp., Japan; Estelite Pro A2E, Tokuyama Dental Corp., Japan; Kalore E2, GC Corporation, Japan; and Clearfil Majesty ES-2 Premium A2E, Kuraray Noritake Dental Inc., Japan) were studied in bovine enamel [ 39 ]. The study found that the enamel margin configuration affected colour adjustment at the borders of the restoration with the bevel preparation improving colour adjustment at the borders [ 39 ].…”
Section: Composite Resin Placement and Colour Adjustment At The Toothmentioning
confidence: 99%
“…Three types of enamel margin (non-bevel, 45-degree bevel and 45-degree reverse-bevel) and four composite resin materials (Estelite Asteria A2B, Tokuyama Dental Corp., Japan; Estelite Pro A2E, Tokuyama Dental Corp., Japan; Kalore E2, GC Corporation, Japan; and Clearfil Majesty ES-2 Premium A2E, Kuraray Noritake Dental Inc., Japan) were studied in bovine enamel [ 39 ]. The study found that the enamel margin configuration affected colour adjustment at the borders of the restoration with the bevel preparation improving colour adjustment at the borders [ 39 ]. With regards to the four composite resin materials, they had different values for straight-line light transmission and light diffusivity within the materials and the degree of colour adjustment at the borders of the restoration was material dependent [ 39 ].…”
Section: Composite Resin Placement and Colour Adjustment At The Toothmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the outputs of the camera are linearly transformed into device-independent XYZ tristimulus values [15][16][17] . The authors demonstrated that enamel margin configuration affected color shifting of the resin composite in the cavity and improved color adjustment at the border of resin composite restorations 18) . Therefore, the purpose of this study was to investigate the influence of the enamel prism orientations on the color adjustment potential of resin composite restorations by evaluating color shifting at the enamel-composite border on the coronal and cervical sides in resin composite restorations in labial surface cavity using a CIE XYZ camera (RC500).…”
Section: Introductionmentioning
confidence: 99%